The effect of social capital on local suppliers’ exploitative and exploratory learning in global buyer-supplier relationships: The moderating role of contract specificity - Wang, L.; Terziovski, Mile; Jiang, Fuming; Li, Jun (Blackwell Publishing Inc., 2017)
Drawing on the theories of social capital (SC) and organizational learning, a contingency theoretical framework that examines the impact of structural, relational, and cognitive SC on local suppliers’ exploitative and exploratory learning in the context of global buyer–supplier (GBS) relationships in China was developed. The extent to which the impact is moderated by the contract specificity between the buyer and supplier is also examined. The empirical results show significant positive impacts of structural and relational SC on local suppliers’ exploitative learning but significant negative impacts on local suppliers’ exploratory learning. More specifically, contract specificity strengthens the positive effects of all three dimensions of SC on exploitative and the negative effects of structural SC and relational SC on exploratory learning. They put forward several potential implications for practicing managers and policymakers.